Algoritmična personalizacija kot izziv in premislek (za družbo) - Praprotnik, Tadej (Monitor ISH, 2022)
The article focuses on the processes of algorithmization at the level of everyday life and presents the socio-cultural consequences of modern, and increasingly present, algorithmic recommendations. Algorithmic recommendations have the power to structure the likelihood of future events and create future actions of individuals. The text presents algorithms as technological infrastructure of everyday life, which enables and defines versions of modern sociality. It presents the social construction of algorithms. The article defines algorithms, introduces the technological architecture on which these algorithms are based, and exposes various social problems that we have recently been addressing through the term algorithmic personalization. Algorithmic recommendations reflect statistical correlations and probabilities for the population (category) but not for the person receiving the recommendations. Their statistical objectivity and reliability significantly simplify, and at the same time limit, an individual‘s perception of the world. For a more comprehensive understanding of modern life, it is essential to treat algorithms as an everyday component and to understand algorithms as a socio-technical option that structures and shapes our daily lives. This can also be the starting point for pursuing different algorithms when we accept the fundamental algorithmicity of everyday life and society
Keywords: algorithms; algoritmi; communication technologies; consumers; datafication; komunikacijska tehnologija; personalizacija; personalization; potrošniki; upodatkovljenje